Hochwasser, Auenlehm und vorgeschichtliche Siedlung: Ein Beitrag auf der Grundlage des Wesergebietes - Nietsch, H. (ERDKUNDE, 1955)
An investigation of the floods of the middle Weser river during the last century and the meteorological conditions which brought them about, showed a clear relationship between severity of winters and increased frequency as well as magnitude of flooding. Two types of floods are distinguished: those mainly due to proceeding frost and those largely resulting from rain, both occurring during the winter months and transitional seasons. Real summer floods are rare. Nevertheless their proportion of the total must have been higher before superposition of the haugh-loam, the most recent sediment on the flood plain. Before the origin of the haugh-loam conditions were less favourable for complete flooding of the valleys, partly because of greater variation in the relief of the valley floors together with the more balanced regime of a still largely wooded region, and partly as a consequence of less severe winters during the Post-glacial period of a climatic optimum which made frost-conditioned floods a rarity. Thus even the proof of existence of prehistoric settlements on she flood plain, before it became covered by haughloam, does not justify the conclusion that the climate was drier during the time of their existence. The origin of the haugh-loam along the Weser can be traced bade to prehistoric times by means of archaeological finds, but a more precise dating of the beginning of its formation is not certain. It is very likely that the haughloam layer experienced various changes during its formation which explains certain contradictions in an attempt to establish a chronology by means of archaeological finds. Pollen analyses show that filling in of river beds by clayey deposits was occurring during the Atlantic Period but they do not exclude the possibility that the haugh-loam layer is more recent. The beginning of haugh-loam deposition is explained by the co-action of hydrological tendencies in respect of flood plain formation and the consequences of changes in the forest cover due to man’s intervention; but further clarification is needed. The pollen analyses on profiles in former branches of the Weser near Schlüsselburg on the middle Weser gave no indications of any noteworthy accumulation on the valley floor before the deposition of the haugh-loam and an insignificant sandy layer beneath, which dates back at least to the Late-Boreal Period.